Paediatric acute liver failure: A prospective, nationwide, population-based surveillance study in Germany - Lenz, Dominic; Abdulaziz, Muhammad; Peters, Bianca; Wagner, Matias; Schlieben, Lea D.; Corman, Victor M.; Baumann, Ulrich; Bufler, Philip; Dattner, Tal; Ganschow, Rainer; Genzel, Kristin; Hammann, Nicole Irene; et al. (Journal of pediatric gastroenterology and nutrition, 2025)
Objectives Paediatric acute liver failure (PALF) is a rare but life-threatening condition, yet comprehensive epidemiological data in Germany are lacking. Our study aimed to systematically analyse incidence, aetiology, and outcome of PALF in Germany. Methods In a nationwide, population-based surveillance study, cases of PALF (defined following the PALF study group inclusion criteria) were queried from 2016 to 2018 through the German Paediatric Surveillance Unit (ESPED). Demographic, clinical, laboratory, therapeutic, and outcome data were collected and analysed. In case of unexplained aetiology, whole exome and virus sequencing was offered as a complementary diagnostic. Results Over the 3-year period, 148 cases were reported, yielding an estimated incidence of 3.7 per 1 million children per year. Neonates and infants were predominantly affected (45% of the cases); median age at PALF was 1.2 years (range: 0-17.9 years). Metabolic/genetic diseases were the most common cause (23%), followed by infectious causes (17%). The overall diagnostic yield was 73%, diagnosis remained unknown in 40 cases. Clinical outcome was age-dependent: new-borns showed a significant higher lethality (42%), followed by infants (29%), toddlers (15%), and school children (12%). Liver transplantation was reported in 22% of cases. Conclusions This study provides comprehensive insights into PALF epidemiology in Germany. Metabolic/genetic causes and infectious diseases were most common. Advances in standardised diagnostic work-up and genetic analysis have enhanced diagnostic yield, yet mortality remains substantial, particularly among neonates. Further research is warranted to improve diagnostic accuracy, therapeutic outcomes, and overall management of PALF.
Gesehen am 07.07.2025